The global role of bioassessment in policy delivery and decision-making for inland waters - Martyn G. Kelly; Gary Free; John P. Simaika; Stuart Warner; Andreas Bruder; Alejandra Correa-Bedoya; Fabio de Oliveira Roque; Tor Erik Eriksen; Jennifer Lento; Craig R. Macadam; Kristian Meissner; Marcelo S. Moretti; et al. (Journal of Environmental Management, 2025)

Capacity challenges in water quality monitoring: understanding the role of human development - Sabrina Kirschke; Tamara Avellán; Ilona Bärlund; Janos J. Bogardi; Laurence Carvalho; Deborah Chapman; Chris W. S. Dickens; Kenneth Irvine; SungBong Lee; Thomas Mehner; Stuart Warner (Environmental Monitoring and Assessment, 2020)
Monitoring the qualitative status of freshwaters is an important goal of the international community, as stated in the Sustainable Development Goal (SDGs) indicator 6.3.2 on good ambient water quality. Monitoring data are, however, lacking in many countries, allegedly because of capacity challenges of less-developed countries. So far, however, the relationship between human development and capacity challenges for water quality monitoring have not been analysed systematically. This hinders the implementation of fine-tuned capacity development programmes for water quality monitoring. Against this background, this study takes a global perspective in analysing the link between human development and the capacity challenges countries face in their national water quality monitoring programmes. The analysis is based on the latest data on the human development index and an international online survey amongst experts from science and practice. Results provide evidence of a negative relationship between human development and the capacity challenges to meet SDG 6.3.2 monitoring requirements. This negative relationship increases along the course of the monitoring process, from defining the enabling environment, choosing parameters for the collection of field data, to the analytics and analysis of five commonly used parameters (DO, EC, pH, TP and TN). Our assessment can be used to help practitioners improve technical capacity development activities and to identify and target investment in capacity development for monitoring.

Unmanned Aerial Systems (UAS) for environmental applications special issue preface - Anita Simic Milas; Joaquim João Sousa; Timothy A. Warner; Ana Cláudia Teodoro; Emanuel Peres; José Alberto Gonçalves; Jorge Delgado Garcia; Ricardo Bento; Stuart Phinn; Amy Woodget (International Journal of Remote Sensing, 2018)